Are COPD Prescription Patterns Aligned with Guidelines? Evidence from a Canadian Population-Based Study - Bahremand T; Etminan M; Roshan-Moniri N; De Vera MA; Tavakoli H; Sadatsafavi M (International Journal of COPD, 2021)
Taraneh Bahremand,1 Mahyar Etminan,2 Nardin Roshan-Moniri,1 Mary A De Vera,1 Hamid Tavakoli,1 Mohsen Sadatsafavi1 1Collaboration for Outcomes Research and Evaluation, Faculty of Pharmaceutical Sciences, The University of British Columbia, Vancouver, BC, Canada; 2Department of Ophthalmology, Faculty of Medicine, The University of British Columbia, Vancouver, BC, CanadaCorrespondence: Mohsen SadatsafaviFaculty of Pharmaceutical Sciences, University of British Columbia, Vancouver, BC, CanadaEmail msafavi@mail.ubc.caBackground: In contemporary guidelines for the management of Chronic Obstructive Pulmonary Disease (COPD), the history of acute exacerbations plays an important role in the choice of long-term inhaled therapies. This study aimed at evaluating population-level trends of filled inhaled prescriptions over the time course of COPD and their relation to the history of exacerbations.Methods: We used administrative health databases in British Columbia, Canada (1997– 2015), to create a retrospective incident cohort of individuals with diagnosed COPD. We quantified long-acting inhaled medication prescriptions within each year of follow-up and documented their trend over the time course of COPD. Using generalized linear models, we investigated the association between the frequent exacerbator status (≥ 2 moderate or ≥ 1 severe exacerbation(s) in the previous 12 months) and filling a prescription after a physician visit.Results: 132,004 COPD patients were included (mean age 68.6, 49.2% female). The most common medication class during the first year of diagnosis was inhaled corticosteroids (ICS, used by 49.9%), followed by long-acting beta-2 adrenoreceptor agonists (LABA, 31.8%). Long-acting muscarinic receptor antagonists (LAMA) were the least commonly prescribed (10.4%). ICS remained the most common prescription throughout follow-up, being used by approximately 50% of patients during each year. 39.0% of patients received combination inhaled therapies in their first year of diagnosis, with ICS+LABA being the most common (30.7%). The association with exacerbation history was the most pronounced for triple therapy with an odds ratio (OR) of 2.68 for general practitioners and 2.02 for specialists (p< 0.001 for both). Such associations were generally stronger among GPs compared with specialists, with the exception of monotherapy with LABA or ICS.Conclusion: We documented low utilization of monotherapies (specifically LAMA) and high utilization of combination therapies (particularly ICS containing). Specialists were less likely to consider exacerbation history in the choice of inhaled therapies compared with GPs.Keywords: COPD, prescription, medication, exacerbation, time trend